The Effect of Work-Family Enrichment on Job Satisfaction of Working Mothers - Ni Made Dwi Puspitawati; Ni Putu Cempaka Dharmadewi Atmaja (AIBPM Publisher, 2020)
Job satisfaction is a crucial problem for working mothers because they must be able to manage two roles well so that it does not impact their work. Role accumulation theory explains how the dual role of a woman in managing their role so that the work they carry out can improve the quality of family life. This study aims to determine the effect of work-family enrichment on work engagement and job satisfaction of working mothers at private universities in Bali. The population is all working mothers who work as lecturers at universities in Bali, totaling 153 people with predetermined population criteria. The sample in this study is the same as the population, but only 145 questionnaires can be used. The analysis tool uses SEM-AMOS. The results showed that (1) work-family enrichment has a positive and significant effect on job satisfaction, (2) work-family enrichment has a positive and significant effect on work engagement (3) work engagement has a positive and significant effect on job satisfaction. The implication of this research is to increase job satisfaction of working mothers, a high work-family enrichment is needed to encourage an increase in employee work engagement.